Research and innovation as a catalyst for food system transformation. (January 2021) - den Boer, A.C.L.; Kok, K.P.W.; Gill, M.; Breda, J.; Cahill, J.; Callenius, C.; Caron, P.; Damianova, Z.; Gurinovic, M.; Lähteenmäki, L.; Lang, T.; Sonnino, R.; et al.
Abstract: Background: Food systems are associated with severe and persistent problems worldwide. Governance approaches aiming to foster sustainable transformation of food systems face several challenges due to the complex nature of food systems. Scope and approach: In this commentary we argue that addressing these governance challenges requires the development and adoption of novel research and innovation (R&I) approaches that will provide evidence to inform food system transformation and will serve as catalysts for change. We first elaborate on the complexity of food systems (transformation) and stress the need to move beyond traditional linear R&I approaches to be able to respond to persistent problems that affect food systems. Though integrated transdisciplinary approaches are promising, current R&I systems do not sufficiently support such endeavors. As such, we argue, we need strategies that trigger a double transformation – of food systems and of their R&I systems. Key Findings and Conclusions: Seizing the opportunities to transform R&I systems has implications for how research is done – pointing to the need for competence development among researchers, policy makers and society in general – and requires specific governance interventions that stimulate a systemic approach. Such interventions should foster transdisciplinary and transformative research agendas that stimulate portfolios of projects that will reinforce one another, and stimulate innovative experiments to shape conditions for systemic change. In short, a thorough rethinking of the role of R&I as well as how it is funded is a crucial step towards the development of the integrative policies that are necessary to engender systemic change – in the food system and beyond. Highlights: Research and Innovation (R&I) could be a catalyst for food system transformation. This requires stimulation of transformative and transdisciplinary R&I approaches. Current conventional R&I systems do not support such R&I approaches. Thus, we need strategies that trigger transformation of both food and R&I systems. This has implications for research practice and requires governance interventions.